The laser plume: is it a health hazard? - Jacques, Agnes (Operating Room Nurses Association of Canada Journal, 1989)
The controversial issue of second-hand cigarette smoke has taken on added signiﬁcance since research has shown it to be harmful to individuals who do not smoke but who are exposed to it on a secondary basis. In this instance, segments of society have decided to take action and fight for their right to a smoke free environment.